2020
DOI: 10.21203/rs.3.rs-22277/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence and Socioeconomic inequalities trends in child health comparing within and between group inequalities: Food insecurity and malnutrition in Zimbabwe

Abstract: BackgroundInequalities in child health remain a threat to this global efforts to achieve universal health coverage. We assessed socioeconomic inequalities in child health focusing on malnutrition and food insecurity in Zimbabwe.MethodsWe used Demographic Health Survey (DHS) data sets of 2010\11 and 2015. Food insecurity in children was determined based on the WHO dietary diversity score. Minimum dietary diversity was defined by a cut- off point of >4 therefore, in this study children with less than 3 of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Our study also reported high food insecurity prevalence among poor rural nourished children whose mothers had attained at least secondary education for both countries. The observed disproportionate health inequalities reported in India and argue that, even though children were receiving nutritious food, challenges in food access were being experienced; this was also observed in other studies [35,58,62,63]. Computed concentration curves for food security status in India and South Africa were all negative, indicating that children from wealthy households were food secure, concurring with findings in the literature [7,22,29,32,37,58,[62][63][64][65][66].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Our study also reported high food insecurity prevalence among poor rural nourished children whose mothers had attained at least secondary education for both countries. The observed disproportionate health inequalities reported in India and argue that, even though children were receiving nutritious food, challenges in food access were being experienced; this was also observed in other studies [35,58,62,63]. Computed concentration curves for food security status in India and South Africa were all negative, indicating that children from wealthy households were food secure, concurring with findings in the literature [7,22,29,32,37,58,[62][63][64][65][66].…”
Section: Discussionsupporting
confidence: 85%
“…The observed disproportionate health inequalities reported in India and argue that, even though children were receiving nutritious food, challenges in food access were being experienced; this was also observed in other studies [35,58,62,63]. Computed concentration curves for food security status in India and South Africa were all negative, indicating that children from wealthy households were food secure, concurring with findings in the literature [7,22,29,32,37,58,[62][63][64][65][66]. The differences between quantity and quality dietary intake among children have been widely documented in literature [7,[64][65][66][67].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations